Femoral Head Detection in Perthes MR Slices with Circular Hough Transform - Memis, Abbas; Albayrak, Songul; Bilgili, Fuat (IEEE, 2018)
In this paper, we present a study on automatic detection of center coordinate and radius of femoral heads in coronal MR slices belong to the patients with Legg-Calve-Perthes (LCP) disease. LCP which lead to dysfunction caused by the deformity of the spherical structure of the femoral head in hip joint is a hip disorder in pediatric orthopaedics. Especially in segmentation studies, automatic detection of femoral head is an important issue in the assessment and quantification studies of the hip diseases. So that, we aimed to detect the healthy and pathological femoral heads in MR slices of LCP patients by using the Circular Hough Transform (CHT) in this study. In this context, first the MR sections are divided vertically into two equal halves to separate the hip joints and then edge images are obtained by using Canny's edge detection method. Finally, femoral heads are detected by performing the CHT on edge images. Successful results were achieved in experiments on healthy and pathological hip joints in 24 coronal MR images belong to 13 patients and the observed outputs were compared.
Keywords: medical image processing; Legg-Calve-Perthes; circular Hough transform; femoral head detection; Engineering; Telecommunications